Profil Perempuan Urban dalam Novel Celebrity Wedding karya Alia Azalea - Rani Anggraini; Hasanuddin WS Hasanuddin WS (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
This study aims to describe the profile of urban women in the metropolitan novel Alia Azalea Celebrity Wedding based on basic attitudes (1) love, (2) beauty, (3) suffering, (4) justice, (5) view of life, (6) responsibility, (7) anxiety, (8) hope. This type of research is qualitative research using descriptive methods. The data in this study are in the form of words, phrases, clauses, sentences which can be formulated as a profile of urban women. Based on the research results, it can be concluded that there are eight basic human attitudes towards female characters in the novel. Eight basic attitude patterns of love that are oriented towards the balance between love for family, fellow human beings and the opposite sex, beauty is oriented towards spiritual beauty, suffering is oriented towards suffering as a trial, justice is oriented towards honesty, view of life is oriented towards a view of life that comes from reflection, responsibility Responsibility is oriented towards self-responsibility, anxiety is oriented towards anxiety in the form of uncertainty, and expectations are oriented towards acceptance expectations in the family environment from Revel.